2023
DOI: 10.3390/healthcare11040483
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Metabolic Risk Factors for Noncommunicable Diseases among Population in the Republic of Srpska (Bosnia and Herzegovina)

Abstract: Noncommunicable diseases (NCDs) are the major cause of death worldwide, and they are attributable to genetic and physiological determinants, behavioral risk factors and environmental impacts. The aim of this study is to assess behavioral risk factors for metabolic disease using demographic and social–economic aspects of the population characterized by risk factors, and to investigate relations among lifestyle risk factors (alcohol consumption, tobacco use, physical inactivity, intake of vitamins, fruits and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
5
2
Order By: Relevance
“…10 The results from Nepal and Bosnia showed higher use of smoked tobacco product daily than in this study. 7,11 The study showed 13.2% were currently using a smokeless tobacco which contrasts the results of study done in Tamilnadu and Haryana of India, Kathmandu, Nepal and assessment from Bangladesh. [7][8][9]12 According to the finding of this study, exposure to second hand smoking at home and work place is found to be 18.4% and 1% respectively.…”
Section: Behavioral Risk Factorscontrasting
confidence: 63%
See 1 more Smart Citation
“…10 The results from Nepal and Bosnia showed higher use of smoked tobacco product daily than in this study. 7,11 The study showed 13.2% were currently using a smokeless tobacco which contrasts the results of study done in Tamilnadu and Haryana of India, Kathmandu, Nepal and assessment from Bangladesh. [7][8][9]12 According to the finding of this study, exposure to second hand smoking at home and work place is found to be 18.4% and 1% respectively.…”
Section: Behavioral Risk Factorscontrasting
confidence: 63%
“…This is higher than the results from Kavre and Kathmandu of Nepal, and different regions of India and lower than that of Vietnam and Bosnia. 4,7,10,11,14 this study, 25.83% of respondents were involved in heavy episodic drinking. This is similar to the finding of Thaha Maknwanpur and opposes to study conducted in Kavre, Kathmadu of Nepal and the India NCD survey.…”
Section: Behavioral Risk Factorsmentioning
confidence: 69%
“…The results showed that the prevalence of metabolic risk factors, including age, smoking, alcohol consumption, and work status, was more pronounced in men and was related to high blood pressure, overweight and obesity, cholesterol level, and blood glucose level. 2 In the Thailand National Health Security Office program, the prevalence of hypertension among men was found to be 37.8%, of which 23.9% of cases were uncontrolled. 3 Established mechanisms associated with the development of hypertension include hyperhomocysteinemia (plasma concentration ≥ 15 µmol/L), which is recognized as a risk factor for cardiovascular diseases including the onset of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Non-communicable diseases (NCDs) are the most common causes of long-term illness, disability and premature death worldwide (Majić et al, 2023). PTM is considered a disease that does not involve microbial influence and is only influenced by lifestyle factors (Budreviciute et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the majority of NCDs are caused by risk factors. which can be prevented (Majić et al, 2023). Non-communicable diseases target all groups, men, women, children, and people in all groups with the condition that someone may look healthy, but they may suffer from these diseases.…”
Section: Introductionmentioning
confidence: 99%